Association of dietary fiber and depression symptom: A systematic review and meta-analysis of observational studies. (January 2021) - Fatahi, Somaye; Matin, Shakiba Shoaee; Sohouli, Mohammad Hassan; Găman, Mihnea-Alexandru; Raee, Pourya; Olang, Beheshteh; Kathirgamathamby, Vaani; Santos, Heitor O.; Guimarães, Nathalia Sernizon; Shidfar, Farzad
Highlights: A potential relationship between depression and the intake of dietary fiber has been hypothesized in several studies. An increased intake of total dietary fiber is associated with lower odds of depression. Common mechanisms included: Changes in the composition of the intestinal microbiome and the reduction of oxidative stress. Abstract: Background: A potential relationship between depression and the intake of dietary fiber has been hypothesized in several studies. However, no meta-analysis has been conducted so far to explore the association between these two variables. Hence, we designed the present meta-analysis to elucidate the relationship between the intake of dietary fiber and depression. Methods: A comprehensive search was performed using the PubMed/Medline, Scopus, Web of Science and Google Scholar databases to identify any relevant studies published from inception to October 2019. Observational studies (cross-sectional and case-control) were included in the analysis. Results: Pooled analysis from the random-effects model of four case-control studies revealed that the consumption of dietary fiber in patients with depression was significantly lower versus healthy controls (WMD: -1.41 mg/dl, 95 % CI: −2.32, −0.51, P = 0.002). No significant heterogeneity was demonstrated among the analyzed studies (I 2  = 4.0 %, P = 0.37). By pooling 5 effect sizes of cross-sectional studies (with a total of 97, 023 subjects), we demonstrated that a higher dietary consumption of fiber was associated with significantly lower odds of depression (OR = 0.76; 95 % CI: 0.64, 0.90; P = 0.010), with a low heterogeneity seen among the retrieved studies (I 2  = 43.9 %; P = 0.12). Conclusion: An increased intake of total dietary fiber is associated with lower odds of depression. Further studies are needed to evaluate the relationship between the different types of dietary fiber and depression.